Implementasi Media Pembelajaran Canva Terhadap Motivasi Belajar Bahasa Indonesia SD - Annisa Asmi; Adini Rahmi; Alya Atsilah Syahni; Adinda Aurelia Azuhra; Cindy Marsya Putri; Affi Fatu Rahmi; Reinita Reinita; Salmaini Salmaini (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Merdeka learning is a goal of the Merdeka Curriculum to improve student skills, create technology-based learning, create innovation in learning and integrate 21st century learning. One aspect of integrating the 21st century is the use of innovative digital learning media using Canva. With Canva, the presentation of the material certainly has an impact on student motivation. With motivation, students are eager to learn and the expected results will be realised. Bringing motivation in students is an important aspect in learning Indonesian.